Monitoring Mediterranean high mountain vegetation in Sistema Central: GLORIA project and collateral ecological studies - Gutiérrez Girón, Alba; Gavilán, Rosario G. (Lazaroa, 2013)
Mediterranean high-mountain ecosystems are considered to be among the most vulnerable to global change. Nevertheless Mediterranean high-mountain ecosystems are still relatively little known and their structure and function have only been elucidated in last decade. High-mountain environments are also currently target ecosystems for monitoring the changes caused by global change. Specifically the GLORIA project has developed a common long-term survey protocol of plant biodiversity changes in these habitats. Other short-term studies can be combined with long-term protocols and make use of the data already available in order to increase the understanding of these habitats and to predict the future responses of communities to global change. We summarized the most relevant results already achieved with short-term studies using the data recorded with GLORIA protocols in Sistema Central.